Nanoengineering : the skills and tools making technology invisible - Berger, Michael (Founder of Nanowerk) (Royal Society of Chemistry, 2020)
While our five senses are doing a reasonably good job at representing the world around us on a macro-scale, we have no existing intuitive representation of the nanoworld, ruled by laws entirely foreign to our experience. This is where molecules mingle to create proteins; where you wouldn't recognize water as a liquid; and where minute morphological changes would reveal how much 'solid' things, such as the ground or houses, are constantly vibrating and moving. Following in the footsteps of Nano-Society and Nanotechnology: The Future is Tiny, this title introduces a new collection of stories demonstrating recent research in the field of nanotechnology. This drives home the fact that a plethora of nanotechnology R & D will become an integral part of improved and entirely novel materials, products, and applications yet will remain entirely invisible to the user. The book gives a personal perspective on how nanotechnologies are created and developed, and will appeal to anyone who has an interest in the research and future of nanotechnology. Reviews of Nanotechnology: The Future is Tiny: 'The book is recommended not only to all interested scientists, but also to students who are looking for a quick and clear introduction to various research areas of nanotechnology' Angew. Chem., 2017, 56(26), 7351-7351 'Once you start reading you will find it very difficult to stop' Chromatographia, 2017, 80, 1821.
Keywords: Nanotechnology.; Nanostructured materials.; elektronické knihy; electronic books